Extraction of tomato by-products’ bioactive compounds using ohmic technology - Coelho, Marta; Pereira, Ricardo; Rodrigues, António S.; Teixeira, José A.; Pintado, Manuela E. (Food and bioproducts processing, 2019)
Tomato peels and seeds are the main by-products of the tomato industry and represent an interesting source of bioactive compounds (BC) including carotenoids, which can be then used as colorant to commercial aquaculture. The aim of the present work was to optimize the extraction of BC from tomato by-products using Ohmic heating (OH) technology. OH extraction experiments were done in the presence of moderate electric fields (MEF) of different intensity (i.e. 4, 6 and 11 V cm−1) to identify the presence of non-thermal effects on the extraction process and its influence on bioactive properties of the extracted compounds. Polyphenol extraction using OH was successfully optimized with the best extraction conditions being 70 °C for 15 min using 70% ethanol as a solvent, which exhibited rutin recovers of 77% higher than control samples. It allowed to recover up to 4.93 μg/gFW lycopene from tomato by-products without resorting to organic solvents. OH can be used as an environmental-friendly, fast and economic process to polyphenols recover from industrial tomato by-products. In addition, the use of different MEF during extraction shows to have a high potential to cause different levels of permeabilization and cell stress that can help to define a selective extraction process of valuable components from tomato by-products.